KUALITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN SINDUE KABUPATEN DONGGALA - Ardiansyah, Ardiansyah; Pasinringi, Andi; Sastrio, Sastrio (Katalogis, 2019)
This study aims to determine how the Quality of Integrated District Administrative Services (PATEN) in Sindue District Office Donggala Regency. This research is a descriptive study with a qualitative approach that is by describing and describing events and phenomena that occur in the field and presents data systematically, factually, and accurately regarding the facts or phenomena that occur in the field. Data collection is done by observation, interview, and documentation techniques. The researcher used triangulation techniques and sources to check the validity of the research data. Data analysis in this study uses four components consisting of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the quality of public services in the Sindue District Office in Donggala Regency uses the dimensions of direct evidence (Tangibles), Realiability, Responsiviness, Assurance and Empathy along with the indicators. Of the five dimensions, there are things that have run optimally, namely responsiveness and Empathy, but there are some indicators that have not been optimal in the quality of services, namely direct evidence Tangibel in this indicator, but it is clear that the availability of facilities and infrastructure to support services still not maximal, Reliability is still constrained by the expertise of officers in this case employees who provide services that are not in accordance with the scientific qualifications possessed and Assurance has not been able to maximize services related to service publishing.